Immune System Links Psoriasis-Mediated Inflammation to Cardiovascular Diseases via Traditional and Non-Traditional Cardiovascular Risk Factors - Kolliker Frers, Rodolfo Alberto (2017)
cular diseases though the reasons are not clear. Here we discuss the role of the immune system in atherosclerosis and of the proinflammatory status in psoriasis and psoriatic arthritis diseases. Methods. We performed a Pubmed query covering publications within the last ten years including epidemiological studies, cross-sectional case-control studies, and reviews. Articles were selected according critical associations using arthritis, immune-mediated inflammatory diseases, and psoriasis as key fields. These were crossed and combined with atherogenesis, endothelial dysfunction, intima-media thickness, subclinical atherosclerosis, plaque, thrombosis, thrombus, fibrinolysis, coagulation, and reactive oxygen species, all closely related to cardiovascular diseases. Both types of disease selected terms were separately combined with cardiovascular risk factors both non-traditional (innate and adaptive pro- and anti-inflammatory immune molecules and cells), and traditional (metabolic conditions and related molecules). Results and conclusions. Immune-activated crossroads came out as the main contributors to proatherogenic inflammation in psoriasis and psoriatic arthritis disease. Traditional and non-traditional cardiovascular risk factors´ interactions result from an active cross-talk between proatherogenic mediators derived from metabolic, vascular and autoimmune joint and skin inflammation in target tissues. Consistently, psoriasis and psoriatic arthritis diseases offer an invaluable scenario to deepen our knowledge on atherosclerotic cardiovascular disease.